2011
DOI: 10.1101/gad.2050711
|View full text |Cite
|
Sign up to set email alerts
|

The yeast rapid tRNA decay pathway primarily monitors the structural integrity of the acceptor and T-stems of mature tRNA

Abstract: tRNAs, like other RNAs, are subject to quality control steps during and after biosynthesis. We previously described a rapid tRNA degradation (RTD) pathway in which the 59-39 exonucleases Rat1 and Xrn1 degrade mature tRNA Val(AAC) C. To understand how the RTD pathway selects substrate tRNAs among different tRNAs lacking the same modifications, we used a genetic screen to examine tRNA Ser(CGA) variants. Our results suggest that RTD substrate recognition in vivo depends primarily on the stability of the accepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
174
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(181 citation statements)
references
References 55 publications
(72 reference statements)
7
174
0
Order By: Relevance
“…Rapid tRNA Decay. Additional levels of tRNA quality control involve the degradation of improper tRNAs by both the nuclear surveillance pathway (37,38) and the RTD pathway (39)(40)(41). To learn whether the aberrant tRNAs that we identified are substrates for cytoplasmic RTD by the 5′-3′ exonuclease Xrn1, we used RT-PCR studies in xrn1Δ cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid tRNA Decay. Additional levels of tRNA quality control involve the degradation of improper tRNAs by both the nuclear surveillance pathway (37,38) and the RTD pathway (39)(40)(41). To learn whether the aberrant tRNAs that we identified are substrates for cytoplasmic RTD by the 5′-3′ exonuclease Xrn1, we used RT-PCR studies in xrn1Δ cells.…”
Section: Resultsmentioning
confidence: 99%
“…The cytoplasmic RTD pathway monitors the tRNA tertiary structure, degrading tRNAs that possess destabilized acceptor and T stems, often because they lack certain modification(s) (39)(40)(41). Lack of some modifications may not decrease tRNA stability, and therefore some hypomodified tRNAs that have mistakenly been exported to the cytoplasm may be unrecognized by the cytoplasmic RTD pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the RTD machinery does not degrade some unmodified tRNAs that normally bear the relevant modifications. To address this problem, Whipple et al (2011) compared two tRNA Ser species, both of which are modified by Trm44 and Tan1, but one, tRNA Ser IGA , is not a RTD substrate, whereas the other, tRNA Ser CGA , is a RTD target. In vivo and in vitro data showed that tRNA Ser CGA gained immunity to RTD when nucleotides of tRNA Ser CGA were replaced with tRNA Ser IGA nucleotides that enhanced the stability of the acceptor and T-stems.…”
Section: To 39 Exonucleolyic Degradation By the Rtd Pathwaymentioning
confidence: 99%
“…The nuclear surveillance pathway provides one mechanism; pre-tRNA Met i lacking m 1 A 58 and pre-tRNAs with aberrant 39 ends are polyadenylated by the TRAMP complex and further degraded by the nuclear exosome (Kabada et al 2004;Copela et al 2008;Ozanick et al 2009). The other pathway, the rapid tRNA decay (RTD) pathway, destroys mature tRNAs that lack certain combinations of modifications or tRNAs that bear unstable T or acceptor stems (Chernyakov et al 2008;Whipple et al 2011).…”
mentioning
confidence: 99%